Glucocorticoid receptor-targeted liposomal delivery system for delivering small molecule ESC8 and anti-miR-Hsp90 gene construct to combat colon cancer. (17th February 2021) - Jinka, Sudhakar; Rachamalla, Hari Krishnareddy; Bhattacharyya, Tithi; Sridharan, Kathyayani; Sekhar Jaggarapu, Madan Mohan Chandra; Yakati, Venu; Banerjee, Rajkumar
Abstract: High mortality rate in colon cancer patients is often attributed to late diagnosis. To overcome the conventional chemotherapy associated challenges, chemotherapeutic drugs (single or combination) or genetic drugs are often delivered using ligand-modified delivery systems that selectively target over expressed receptors or particular receptors that act abnormally in cancer cells. In the current investigation, first we assessed anti-colon cancer effect of a cationic estrogenic molecule, ESC8 which was earlier shown to act against estrogen receptor (ER) ± breast cancer cells. We found that against both colon and breast cancer cells the anticancer activity is intervened by AMPK-mTOR pathway and at the same time it acts as anti-angiogenic agent. It also showed enhancement of mesenchymal-to-epithelial (MET) transition as well as reduction of cyclin D in both cells. Earlier we demonstrated the use of glucocorticoid receptor (GR) targeted cationic liposomal delivery system carrying anti-Hsp90 plasmid and ESC8 to act as potent anti-skin cancer therapeutics. As ESC8 demonstrated anti-colon cancer effect in vitro, in here, we used the same GR-targeted liposomal formulation but carrying a more fusogenic cationic lipid D1 and used against colon tumor orthotopic model in mice. We show that GR targeted formulation (D1XE-Hsp90) exhibited efficient cellular uptake, transfection and selective cytotoxicity in colon cancer cells, tumor-targeted bio-distribution and enhanced survivability, reduced tumor size in orthotopic colon tumor-bearing mice. The tumor sections exhibited reduced tumor proliferation as well as neo-vascularization, thus supporting the holistic antitumor effect of the D1XE-Hsp90 formulation. Over all our results establish the GR-targeted D1XE-Hsp90 formulation as potent anti-colon cancer therapeutics.